2021
DOI: 10.1371/journal.pgen.1009570
|View full text |Cite
|
Sign up to set email alerts
|

The DNMT3A PWWP domain is essential for the normal DNA methylation landscape in mouse somatic cells and oocytes

Abstract: DNA methylation at CG sites is important for gene regulation and embryonic development. In mouse oocytes, de novo CG methylation requires preceding transcription-coupled histone mark H3K36me3 and is mediated by a DNA methyltransferase DNMT3A. DNMT3A has a PWWP domain, which recognizes H3K36me2/3, and heterozygous mutations in this domain, including D329A substitution, cause aberrant CG hypermethylation of regions marked by H3K27me3 in somatic cells, leading to a dwarfism phenotype. We herein demonstrate that D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 66 publications
(155 reference statements)
2
19
0
Order By: Relevance
“…Then, upon recruitment, the ADD domains of DNMT3A and DNMT3L recognize H3K4me0, leading to the disruption of the autoinhibitory structure of DNMT3A 5 , 40 . While the DNMT3A PWWP domain does bind to H3K36me2 and H3K36me3, we recently found that DNA methylation still occurs in H3K36me2/3-enriched regions even when a point mutation (D329A) disrupting H3K36me2/3 binding is introduced 45 . Therefore, the DNMT3A-DNMT3L complex could have an additional, uncharacterized mechanism for recognizing H3K36me2/3.…”
Section: Discussionmentioning
confidence: 96%
“…Then, upon recruitment, the ADD domains of DNMT3A and DNMT3L recognize H3K4me0, leading to the disruption of the autoinhibitory structure of DNMT3A 5 , 40 . While the DNMT3A PWWP domain does bind to H3K36me2 and H3K36me3, we recently found that DNA methylation still occurs in H3K36me2/3-enriched regions even when a point mutation (D329A) disrupting H3K36me2/3 binding is introduced 45 . Therefore, the DNMT3A-DNMT3L complex could have an additional, uncharacterized mechanism for recognizing H3K36me2/3.…”
Section: Discussionmentioning
confidence: 96%
“… 57 , 69 ) In growing oocytes, transcriptionally active regions marked with lysine 36-trimethylated H3 (H3K36me3) are the primary target of methylation. 70 74 ) We found that UHRF1 KO showed a 25% reduction in global methylation, predominantly occurring in transcriptionally inactive regions with no H3K36me3. 61 ) This reduction is greater than that observed in DNMT1 KO oocytes.…”
Section: Role Of the Uhrf Protein Family In Mammalian Developmentmentioning
confidence: 81%
“…Epigenetics refers to the stable and inheritable changes in gene expression without alterations in DNA sequences, and is crucially involved in gene regulation, cellular differentiation, gene imprinting, X-chromosome inactivation and other cellular processes [ 18 ]. Previous studies evaluating H3K36me2 observed inconsistent results for recruiting DNMT3A and shaping the intergenic DNA methylation landscape [ 19 ]. Moreover, H3K36me2 could demarcate PRC2-mediated H3K27me2 and H3K27me3 domains in ESCs [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%